Fetal Pollution Exposure, Cognitive Ability, and Gender-Specific Parental Investment - Xin Zhang; Yixuan Wang; Xingyi Hu; Xi Chen (Institute of Labor Economics (IZA), 2024)
This paper examines the impact of fetal exposure to air pollution on low-stakes test performance across a broad age range, with a focus on gender-specific parental responses to this negative shock. Using data from a nationally representative survey in China, we find that fetal PM2.5 exposure significantly reduce cognitive ability in women, particularly those with brothers. Gender-biased human capital investment by families tends to amplify the harmful effects for girls, while diminishing these effects for boys. Specifically, when exposed to the same level of fetal PM2.5, females receive less homework assistance from their families and attain lower levels of education.
Keywords: Q53; I24; D13; J16; 330; air pollution; cognitive ability; fetal exposure; gender bias; parental investment